Response surface optimization of enzymatic hydrolysis and ROS scavenging activity of silk sericin hydrolysates - Keerati Joyjamras; Chatchai Chaotham; Pithi Chanvorachote (Taylor & Francis Group, 2022)
Context Sericin, a protein found in wastewater from the silk industry, was shown to contain a variety of biological activities, including antioxidant. The enzymatic conditions have been continuously modified to improve antioxidant effect and scavenging capacity against various free radicals of silk sericin protein. Objective Variables in enzymatic reactions, including pH, temperature and enzyme/substrate ratio were analysed to discover the optimum conditions for antioxidant activity of sericin hydrolysates. Materials and methods Hydrolysis reaction catalysed by Alcalase® was optimized through response surface methodology (RSM) in order to generate sericin hydrolysates possessing potency for % inhibition on 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals, ferric-reducing power and peroxyl scavenging capacity. Flow cytometry was performed to evaluate cellular ROS level in human HaCaT keratinocytes and melanin-generating MNT1 cells pre-treated either with 20 mg/mL RSM-optimized sericin hydrolysates or 5 mM N-acetyl cysteine (NAC) for 60 min prior exposure with 1 mM hydrogen peroxide (H2O2). Results Among these three variables, response surface plots demonstrate the major role of temperature on scavenging capacity of sericin hydrolysates. Sericin hydrolysates prepared by using Alcalase® at RSM-optimized condition (enzyme/substrate ratio: 1.5, pH: 7.5, temperature: 70 °C) possessed % inhibition against H2O2 at 99.11 ± 0.54% and 73.25 ± 8.32% in HaCaT and MNT1 cells, respectively, while pre-treatment with NAC indicated the % inhibition only at 30.26 ± 7.62% in HaCaT and 51.05 ± 7.14% in MNT1 cells. Discussion and conclusions The acquired RSM information would be of benefit for further developing antioxidant peptide from diverse resources, especially the recycling of waste products from silk industry.